Feasibility study of a novel electrode concept for a neuroprosthesis for augmentation of impaired finger functions - Rósa Hugosdóttir; Skúli Þór Jónasson; Haraldur Sigþórsson; Þórður Helgason (PAGEPress Publications, 2014)
The project "Finger Rehabilitation" aims to design a neuroprosthesis with integrated electronics. The neuroprosthesis should enable spinal cord injured people, with injury at cervical vertebrae level, to increase finger mobility and activity with the use of functional electrical stimulation. The equipment is based on several integrated factors. The user has to be independent from any external help and has to be able to put it on, control the electrical stimulation and remove it by himself. The neuroprosthesis has to be both flexible and stable for the electrodes to remain firmly on the skin. In this part of the project, new electrodes which do not get stuck on the skin are described. The electrodes are small and have low impedance. A sleeve, made from glass fibres, is also described. The electrode matrices are integrated in the sleeve. The neuroprosthesis fits a patient with spinal cord injury at C5-C6. In this work, a novel electrode concept integrated in a glass fibre sleeve is tested on its ability for use in an "independent user" neuroprosthesis for finger movement rehabilitation.